The Effect of Child Abuse on University Student’s Psychological Status: A Retrospective study - M. Azize, Pary; A. Kadir, Farida; Luqman Othman, Lavin (Kurdistan Journal of Applied Research, 2018)
Child abuse commonly underpins adult depression. Child abuse is classified into four categories; physical, sexual, mental and neglect. This paper will study and discuss the rate of depression caused by child abuse at the time of the abuse, the data collected from the first section of the survey, which consisted of two categorical questions. There are two questions that this research will try to answer; have more females experienced one or multiple types of abuse during their childhood compared to male? And have the ones who have experienced abuse suffered from a degree of depression at the time of the abuse. The depression test that consisted of four questions that determined the participant’s depression percentage The result and tables have been duplicated from the Public Service Pension Plan (PSPP), 21 females and 36 males participated in the survey. In total 57 students answered the questions that were sent through email. 73% of the participants said that they were not abused as a child in any of the forms. 27% of the participants have been abused in one or more of the ways as a child., further, 71.4% of the abuse were physical followed by mental and neglect (28%. 28%, respectively). Likely there were zero records of sexual abuse. Most of the abuse was happening around age 1-5 years and less likely on age 1-5 and above. Females become more depressed than males. 57.2% of the abused children were suffering from anxiety followed by an interruption in their relationship and low self esteem It can be concluded that more female were abused as a child. We can see that the constant (Male) is 49.29 and the female participants are 26.34 more than the constant. This proves that females become more depressed than men. Therefore, much work will need to Protect the children from harm.